Distributed consensus algorithms for crossdomain data management: state-of-the-art, challenges and perspectives - Weiming LI; Tong LI; Dafang ZHANG; Longchao DAI; Yunpeng CHAI (大数据)
With the exponential growth of data and the company's cross-domain disaster recovery requirements, companies increasingly need to manage data across spatial domains.Cross-domain data management requires a distributed consensus algorithm to make the data consistent.However, the existing distributed consensus algorithms only consider the situation of a single data center, and do not consider the uncertainty of network communication between data centers, so they face long log synchronization delays and low system throughput in cross-space region scenarios and other issues.The current status and new challenges of distributed consensus algorithms in the cross-space domain were sorted out systematically, and the technical route to solve these challenges was looked forward.